Territorial Rivalries in Humanitarian Work and Nursing: Critical Examination of Professional Identities and Delivery of Care - Janaka Jayawickrama; Jordan Lindekens (Interdisciplinary Journal of Partnership Studies)
This article explores the challenges of professional identities and delivery of care in humanitarian work and nursing practices. Using a twofold methodology comprising a literature review and analysis of two case studies – humanitarian responses to the 2004 tsunami in Sri Lanka and responses to the COVID-19 pandemic in a hospital setting in the USA – the authors highlight how traditional education may fall short in preparing individuals to be compassionate and effective caregivers. This article suggests that drawing on ideas from ancient philosophies beyond the Euro-North American perspective could help to improve learning. By incorporating values like teamwork, joyfulness, openness, and humility, we might create better strategies for training and avoid conflicts within caring professions such as nursing and humanitarianism.